Pengaruh Karakteristik Informasi Dan Sistem Informasi Akuntansi Terhadap Kinerja Manajerial Di Badan Penelitian Dan Pengembangan Provinsi Sumatera Barat - Lathiva Gusna Diva; Elsa Meirina (Universitas Katolik Widya Karya Malang, 2023)
This study aims to explain the influece of informatiomof characteristics and accounting information systems on managerial performance in goverment agencies is the aim of the research. Determination of the sample using the total population sampling method in this study were structural officials and staff at the west sumatera research and development agency and the sample used in this study was as many as 31 respondents. Based on research result that there is an influence of information on characteristics on managerial performance the work of managers of geverments agencies and there is influence of accouting informatios systems on the managerial performance of agencies.